A convenient and mild method for 1, 2, 4-oxadiazole preparation: cyclodehydration of O-acylamidoximes in the superbase system MOH/DMSO. Issue 26 (29th June 2016) - Baykov, Sergey; Sharonova, Tatyana; Osipyan, Angelina; Rozhkov, Sergey; Shetnev, Anton; Smirnov, Alexey
Graphical abstract: Highlights: The new catalyst system for 1, 2, 4-oxadiazole preparation is described. Using the superbase catalytic system 1, 2, 4-oxadiazole formation from O -acylamidoximes takes several minutes at RT. The method can be used for a wide scope of substrates which are stable under the basic conditions. Abstract: Herein, we reported a general, convenient, and efficient synthesis of 3, 5-disubstituted-1, 2, 4-oxadiazoles via cyclodehydration of O -acylamidoximes in the superbase system MOH/DMSO (M = Li, Na, K). Excellent isolated yields (up to 98%) were attained within short reaction times (10–20 min). In addition, mild reaction conditions and a simple work-up procedure allow the synthesis of a wide range of heat-labile 1, 2, 4-oxadiazole-containing substances.